The Evolving History of the Revista de Investigación Clínica - Gerardo Gamba; Enrique Wolpert-Barraza; Alvar Loria; Alfredo Ulloa-Aguirre (Permanyer, 2021)
The Revista de Investigación Clínica (RIC) was established in 1948. It has been published continuously for 73 years. Until 2009, it was the journal of the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (formerly Hospital de Enfermedades de la Nutrición, and later named Instituto Nacional de la Nutrición), and thereafter it became the official journal of the Mexican National Institutes of Health. The history of this journal may be divided into four eras or periods, each distinctly characterized by the trends, and particular editorial policies imposed by the Editor-in-Chief and Editorial Committee in turn. The RIC, since 2015 known as RIC -Clinical and Translational Investigation-, is currently a nationally and internationally recognized scientific journal. This article briefly reviews the most outstanding historical features of the RIC since its foundation.